2020
DOI: 10.21203/rs.3.rs-24602/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determination of the ED95 of intrathecal hyperbaric prilocaine with sufentanil for scheduled cesarean delivery: A dose-finding study based on the continual reassessment method

Abstract: Background – Scheduled cesarean section is routinely performed under spinal anesthesia using hyperbaric bupivacaine. The current study was undertaken to determine the clinically relevant 95% effective dose of intrathecal 2% hyperbaric prilocaine co-administered with sufentanil for scheduled cesarean section, using continual reassessment method.Methods – We conducted a dose-response, prospective, double-blinded study to determine the ED95 values of intrathecal hyperbaric prilocaine used with 2,5 mcg of sufentan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The ED 95 of hyperbaric prilocaine was recently determined by our team to be 50 mg while combined with the same opioids. 19 With respect to motor block regression, the present findings corroborate recent studies, which established the intermediate-action profile of hyperbaric prilocaine. 14,17 Importantly, 2% hyperbaric prilocaine 50 mg allowed complete recovery from motor block 1 h earlier than bupivacaine, thus validating our superiority hypothesis for the primary outcome.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The ED 95 of hyperbaric prilocaine was recently determined by our team to be 50 mg while combined with the same opioids. 19 With respect to motor block regression, the present findings corroborate recent studies, which established the intermediate-action profile of hyperbaric prilocaine. 14,17 Importantly, 2% hyperbaric prilocaine 50 mg allowed complete recovery from motor block 1 h earlier than bupivacaine, thus validating our superiority hypothesis for the primary outcome.…”
Section: Discussionsupporting
confidence: 90%
“…6,7,35 Our results highlight the better haemodynamic profile for prilocaine during C-section, confirming our previous ED 95 study findings. 19 This benefit was not observed by Chapron et al 30 who reported an 80% incidence of hypotension, similar for the two drugs, but this can reasonably be explained by the higher doses, which they used. 30 We did not observe a difference in vasopressor use, probably as we immediately treated nausea or dizziness, commonly considered as prodromes of hypotension, even before obtaining the blood pressure measurement.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations